Analysis Empowerment of Village Communities in Gayo Lues Regency - Ardian, Deddi; Kelana, Edy Putra; Aisyah, Siti (Riwayat: Educational Journal of History and Humanities, 2024)
Village Community Empowerment is a process that aims to increase the ability and capacity of communities at the village level in managing existing resources, meeting basic needs, and playing an active role in development. The utilization of village fund allocations in 148 villages in Gayo Lues district is still not utilized optimally every year for community empowerment activities even though village fund allocations have been provided by the government for each village. This research aims to analyze the empowerment of village communities through the use of village fund allocations and the factors that influence the use of village fund allocations in empowering communities. The theory used is the theory of community empowerment according to Adisasmita with 3 aspects, namely the input aspect (Human Resources, Budget, Facilities and Infrastructure, Data, Planning and Technology), the process aspect (Implementation, Monitoring and Supervision), and the output aspect (Target achievement, Effectiveness and Efficiency). The research results show that the empowerment of village communities through the allocation of village funds in Gayo Lues Regency based on research results has not yet been achieved as expected. The allocation of village funds which is expected to be able to achieve 70% use in the field of community empowerment, is in fact not used optimally by the village government in Gayo Lues Regency. The factor that influences the use of village fund allocations in empowering village communities in Gayo Lues Regency is the inconsistency of village officials in using village fund allocations in community empowerment programs between community proposals during village musrenbang and the realization of the implementation of community empowerment programs.